2021
DOI: 10.3389/fendo.2021.647184
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Abdominal Computed Tomography Scans for Differentiating the Discrepancies in Abdominal Adipose Tissue Between Two Major Subtypes of Primary Aldosteronism

Abstract: The aim of this study was to analyze the differences in the distribution of abdominal adipose tissue between the two subtypes of primary aldosteronism (PA) using abdominal computed tomography. We retrospectively analyzed patients diagnosed as having essential hypertension (EH) or PA from the prospectively collected Taiwan Primary Aldosteronism Investigation (TAIPAI) database. Patients with PA were divided into the subgroups of idiopathic hyperaldosteronism (IHA) and unilateral aldosterone-producing adenoma (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…We also found significant inverse relationships between RSF% and PAC and ARR in the unilateral women even after adjustment for key confounders. Our findings are consistent with previous studies that found epicardial fat thickness and visceral adipose tissue area are negatively associated with PAC and ARR in PA patients with unilateral aldosterone-producing adenoma [ 15 , 41 ]. Although the mechanism responsible for our observation of the dissociation between unilateral and bilateral groups remains unclear, it is possible that abnormally high PAC causes adipose tissue inflammation and fibrosis, leading to the inhibition of RSF expansion in unilateral PA patients [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…We also found significant inverse relationships between RSF% and PAC and ARR in the unilateral women even after adjustment for key confounders. Our findings are consistent with previous studies that found epicardial fat thickness and visceral adipose tissue area are negatively associated with PAC and ARR in PA patients with unilateral aldosterone-producing adenoma [ 15 , 41 ]. Although the mechanism responsible for our observation of the dissociation between unilateral and bilateral groups remains unclear, it is possible that abnormally high PAC causes adipose tissue inflammation and fibrosis, leading to the inhibition of RSF expansion in unilateral PA patients [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although APA leads to higher aldosterone secretion compared to BAH ( 98 ), several reports have revealed higher prevalence rates of MetS, obesity, and dyslipidemia in patients with BAH compared to those with APA ( 97 , 99 101 ). Youichi et al.…”
Section: Kcnj5 Somatic Mutationsmentioning
confidence: 97%
“… 8 , 9 Further studies followed, showing a correlation between renin or aldosterone-to-renin ratio (ARR) and diabetes prevalence, glucose metabolism indices, or visceral fat mass. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Further studies followed, showing a correlation between renin or aldosterone-to-renin ratio (ARR) and diabetes prevalence, glucose metabolism indices, or visceral fat mass. 10,11 Collectively, the relationship between PA and distribution of body fat mass (FM), lean mass (LM) is relatively unexplored area. There is growing support for the notion that regional FM and LM are related to distinct effects on metabolic syndrome and CVD.…”
Section: Introductionmentioning
confidence: 99%